Identificación de los riesgos mecánicos en las prácticas académicas en los talleres de mecánica de la Universidad Tecnológica Equinoccial Sede Santo Domingo, propuesta de prevención. - Zapata Mayorga, Holger Alfredo (2016)
This work was carried out at UTE Santo Domingo, a highly prestigious university for the training of competent professionals. The problem of the research dealt with was related to the evaluation of mechanical risks in a workshop of the Electromechanical and Automotive careers where there are a large number of machines that have a high risk in use. The main objective of the investigation was to determine the relationship between the processes that are carried out in the mechanical workshop of the UTE and the inherent mechanical risks to propose a plan for the prevention of occupational risks, during the year 2016.